English as a Lingua Franca Approach: Implications and Limitations in Saudi English as a Foreign Language Classrooms - Alharbi, Samar (Advances in Social Sciences Research Journal, 2021)
English language considers a global language spoken by a majority of people around the world. It is a language used mainly for communication, trades and study purposes. This widespread of English language being wildly spoken lead to different varieties of English as a lingua franca (ELF) means that non native speakers of English still be able to communicate with each other. Using ELF as a legitimate variety of English in language classrooms is questioned by some researchers. This paper will provide an overview of the concept of ELF. It will also present implications and limitations of using ELF in Saudi English as foreign language classrooms.